The Effectiveness of Blog Media in Improving Student’s Ability in Writing Exposition Text - Ningsih, Fitria; Syafitri, Widya; Syahrul, Syahrul; Irwandi, Irwandi (Journal of Educational Management and Strategy, 2023)
This article was motivated by students who are less active and do not participate in the learning process. The learning process was still teacher-centered. The response of students in learning was still lacking and students do not like English in class XI of SMKN 4 Payakumbuh. Most of the English language scores of students' learning outcomes are still below the KKM 75, in this case, it can be seen from the results of the first semester English exam in SMKN 4 Payakumbuh class. This study aims to determine whether there was a significant difference between students who used learning media using blogs and students who do not used blogs in learning exposition texts at SMKN 4 Payakumbuh. This study used a quantitative approach in the form experiment. The design of this study used was the pretest posttest control group design. The population in this study amounted to 7 classes with a total of 172 students. The number of samples was 2 classes, namely, class XI.TKJ 2 as the experimental class and class XI.TKJ 3 as the control class. The researcher used Simple Random Sampling technique. In this study, the researcher used a normality test and a homogeneity test, while to test the hypothesis; the researcher used a t-test with alpha (0.05). The results of this study indicate that the t-count value of the SPSS results is 6.422 and the t-table value is 2.060 so that t-count> t-table then H0 was rejected and Ha was accepted. It was proved that using blog as writing could help students in improving their ability in writing. Artikel ini dilatarbelakangi oleh peserta didik yang kurang aktif dan kurang berpartisipasi dalam proses pembelajaran. Proses pembelajaran yang masih berpusat pada guru. Respon peserta didik dalam pembelajaran masih kurang dan peserta didik kurang menyenangi bahasa inggris dikelas XI SMKN 4 Payakumbuh. Sebagian besar nilai bahasa inggris hasil belajar peserta didik masih berada dibawah KKM 75 dalam hal ini dilihat dari hasil ujian bahasa Inggris tengah semester I di kelas SMKN 4 Payakumbuh. Penelitian ini bertujuan untuk mengetahui apakah ada perbedaan yang signifikan antar siswa yang menggunakan media pelajaran menggunakan blog dengan siswa yang belajar dengan tidak menggunakan media blog dalam pembelajaran teks eksposisi di sekolah SMKN 4 Payakumbuh. Penelitian ini menggunakan pendekatan kuantitatif dengan bentuk eksperimen. Desain penelitian ini yang digunakan adalah pretest posttest group control design. Populasi dalam penelitian ini berjumlah tujuh kelas dengan banyak siswa seluruhnya 172 siswa. Jumlah sampel sebanyak 2 kelas yaitu, kelas XI.TKJ 2 sebagai kelas eksperimen dan kelas XI.TKJ 3 sebagai kelas kontrol. Peneliti menggunakan teknik Simple Random Sampling. Dalam penelitian ini, peneliti menggunakan tes normalitas dan tes homogenitas, sedangkan untuk menguji hypothesis peneliti menggunakan uji-t dengan alpha (0,05). Hasil penelitian ini menunjukan bahwa nilai t-hitung dari hasil spss sebesar 6,422 dan t-tabel diperoleh nilai sebesar 2.060 sehingga t-hitung>t-tabel maka H0 ditolak dan Ha diterima. Sehingga bisa disimpulkan baha menggunakan media blog dapat membantu siswa dalam meningkatkan kemampuan mereka dalam menulis.